2010
DOI: 10.1002/tal.593
|View full text |Cite
|
Sign up to set email alerts
|

Collapse risk of tall steel moment frame buildings with viscous dampers subjected to large earthquakes

Abstract: The design approach for tall steel moment frame structures with viscous dampers entails sizing steel members per code‐level strength forces, and sizing viscous dampers to limit storey drifts. This method has been used extensively in new and retrofit applications. This methodology has resulted in structures that have longer periods than those using the code‐designed approach, are economically competitive and have excellent performance in design‐level earthquakes. However, the efficacy of this design in extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Criteria for damper failure are based on the compound displacement–force limit states, where the damper is assumed to act as a brace when the peak damper displacement is reached . At this stage, the viscous force in the damper drops to zero, and it only provides stiffness to the structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criteria for damper failure are based on the compound displacement–force limit states, where the damper is assumed to act as a brace when the peak damper displacement is reached . At this stage, the viscous force in the damper drops to zero, and it only provides stiffness to the structure.…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, it is assumed that all components are made of A36 steel with yield and fracture stresses of 250 and 400 MPa, respectively. The length of the piston and cylinder is assumed to be twice the maximum damper stroke, whereas the length of the piston undercut is taken from the literature . The cross‐sectional areas of the cylinder, piston, and undercut are determined by taking the outer diameter of the cylinder to be 28.6 cm and making the following assumptions: (1) the thickness of the cylinder is 10% of the outer cylinder radius; (2) the piston occupies 25% of the cylinder volume; and (3) the area of the piston undercut is 80% of the piston area.…”
Section: Resultsmentioning
confidence: 99%
“…These low-to mid-rise buildings are an important subgroup of structures, because many applications of the SMRF-FVD system are for this type of construction. A companion paper addresses the response of high-rise SMRF-FVD buildings (Miyamoto et al 2010a).…”
Section: Archetypesmentioning
confidence: 99%
“…Patil and Jangid [16] investigated the response of a 76-story benchmark building under across-wind loads. Miyamoto et al [17] studied the collapse risk of tall steel moment-frame buildings (10-, 20-, 30-, and 40-story models) with viscous dampers subjected to severe earthquakes. The analysis showed that during extreme seismic events, the design exhibited satisfactory performance.…”
Section: Introductionmentioning
confidence: 99%